Rehabilitation Medicine Outcome of 51 Years Old Morbus Hansen Patient with Disability at Jayapura Hospital: A Case Report - Ansanay, Rini Lestari; Setyarini, Kaida Irma (PT FORMOSA CENDEKIA GLOBAL, 2025)
Leprosy is a disease that causes high morbidity. Nerve damage due to Mycobacterium Leprae can cause impairment, disability to handicap for individuals. Jayapura is a city with quite high cases of leprosy in Papua. The method used is case report to presenting the case. A case of Leprosy with upper extremity with clawing hand disability due to ulnar nerve disorder will be described and displayed as a medical rehabilitation. The outcome of therapy showed improvements in function, flexibility, motor and sensory function of the upper extremities (metacarpal region). The conclusion of this case report is that disability in leprosy patients can provide improved flexibility and prevention of more severe disability with early detection, holistic management, medical rehabilitation and family support.